THE ROLE OF DIGITAL MARKETING IN INCREASING THE COMPETITIVENESS OF HIGHER EDUCATION (Marketing Journal, 2025)
This article scientifically explores the importance and effectiveness of digital marketing tools in enhancing the competitiveness of higher education institutions. The study analyzes the digital marketing strategies of global universities, assessing the ro le of social media, search engine optimization (SEO), content marketing, and artificial intelligence technologies in attracting students. The findings indicate that effective application of digital marketing strengthens university branding, increases stude nt enrollment, and helps institutions attain higher positions in international rankings.
Keywords: digital marketing; higher education; competitiveness; social media; SEO; content marketing; student recruitment. № 1 115